2000
DOI: 10.1038/sj.cdd.4400785
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal differentiation does not involve the pro-apoptotic executioner caspases, but is associated with caspase-14 induction and processing

Abstract: The epidermis is a stratified squamous epithelium in which keratinocytes progressively undergo terminal differentiation towards the skin surface leading to programmed cell death. In this respect we studied the role of caspases. Here, we show that caspase-14 synthesis in the skin is restricted to differentiating keratinocytes and that caspase-14 processing is associated with terminal epidermal differentiation. The proapoptotic executioner caspases-3, -6, and -7 are not activated during epidermal differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
242
0
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(280 citation statements)
references
References 35 publications
26
242
0
7
Order By: Relevance
“…Using mutant ROCKI or ROCK inhibitors, it was shown that ROCK activity is required to establish a higher-ordered architecture of the actin cytoskeleton during the initial steps of epidermal sheet formation. 25 Since active, processed caspase-3 is not detectable in normal newborn or adult skin, 26,27 it is unlikely that caspase-3 is involved in ROCKI activation during epidermal differentiation. These findings also indicate that ROCKI activity probably requires an apoptotic environment to induce membrane blebbing.…”
Section: Cytoskeleton Rearrangementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using mutant ROCKI or ROCK inhibitors, it was shown that ROCK activity is required to establish a higher-ordered architecture of the actin cytoskeleton during the initial steps of epidermal sheet formation. 25 Since active, processed caspase-3 is not detectable in normal newborn or adult skin, 26,27 it is unlikely that caspase-3 is involved in ROCKI activation during epidermal differentiation. These findings also indicate that ROCKI activity probably requires an apoptotic environment to induce membrane blebbing.…”
Section: Cytoskeleton Rearrangementsmentioning
confidence: 99%
“…55 Although different caspases are expressed in the adult epidermis (caspase-1, -2, -3, -4, -6, -7, -8, -9, -11 and -14), 26,56 evidence that the proapoptotic caspases take part in normal skin formation is absent. Despite an early suggestion that caspase-3 is required for corneocyte formation, 57 several other data point out that apoptotic caspases are not activated during adult keratinocyte cornification.…”
Section: Caspasesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the phenotypes of other knockouts are very severe, are evidently antiapoptotic, and vary from early embryonic lethality (caspase 8), to perinatal lethality (caspases 3 and 9; Kuida et al, 1996Kuida et al, , 1998Varfolomeev et al, 1998), to relatively mild effects with defects in the process of normal oocyte ablation (caspase 2; Morita et al, 2001). Currently, caspase 14 may be the odd man out, being involved in keratinocyte differentiation (Eckhart et al, 2000;Lippens et al, 2000). Humans and mice each contain 11 caspases, and most (if not all) of these are found in the brain, either in neurons or (especially in the case of the inflammatory caspases) in glia.…”
Section: Caspases Are Required For Apoptosismentioning
confidence: 99%